PENGOLAHAN LIMBAH KULIT KAKAO DAN KEMIRI PADA PEMBUATAN BIOPELET SEBAGAI BAHAN BAKAR ALTERNATIF - Purwandari, Vivi; Harahap, Mahyuni; Zai, Liver; Arya Mubarakh, Muhammad (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2022)
The amount of fuel reserves were getting depleted and has created problems with the occurrence of a fuel crisis, which has resulted in higher prices and the economy of the community has been down. Biomass is a renewable alternative fuel source but still has weaknesses, like high water content, low calorific value and low density and the combustion process requires high temperatures. To overcome this problem, biomass can be processed into biopellets with the aim of increasing its density and increasing the quality of combustion. The research was about the processing of cocoa and candlenut shell waste as an alternative fuel in the manufacture of biopellets using tapioca adhesive. The stages of this research include the preparation of raw materials for cocoa shells and candlenut shells ground to a size of 60 mesh and then added with various adhesives of 5%, 10% and 15%, then printed manually and dried in an oven with a temperature of 60oC for ±3 hours. Furthermore, the biopellets were characterized based on the provisions of SNI 8021:2014 which included density, moisture content, ash content, volatile matter, fixed carbon, calorific value with the most optimum values, respectively, 1.02 g/cm3, 3.14%, 6 ,25%, 64.56%, 26.05% and 4145.6 cal/g. Biopellets were also tested for effectiveness such as fracture strength and combustion rates with values of 0.14% and 0.11 g/min, respectively. Biopellet with the best quality was found in the type of biopellet with a mixture of raw materials 2:1 and using 10% tapioca adhesive.